أثر اختلاف القراءات في أحكام الوضوء - el-Bayyoumiy, Ibrahim Mohammed; Zakirman, Al Fakhri (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2022)
ملخص حظيت القراءات باهتمام المسلمين منذ نهضتهم الأولى على يد رسول الله وصحابته الكرام إلى يومنا هذا، فلقد تجرد عدد كبير من علماء المسلمين لخدمة كتاب الله وأفنوا أعمارهم بتتبع كل صغيرة وكبيرة حول هذا العلم وسطروا كل ما جادت به عقولهم وأفكارهم في مؤلفات أصبحت مفخرة للمسلمين، ولكن من الموضوعات التى لم تأخذ حظها من الدراسة بشكل واسع أثر القراءات فى العلوم الأخرى وتأتى هذه الدراسة لتبين أثر اختلاف القراءات القرآنية فى الأحكام الشرعية وتنناول أحكام الطهارة المتعلقة بالوضوء ويشمل الحديث عن أثر اختلاف القراءات القرآنية فى بيان الفرض فى الرجلين هل الغسل أم المسح؟ وتتناول أثر اختلاف القراءات فى حكم نقض الوضوء بلمس المرأة لتبين أن اختلاف القراءات كان له أثر فى اختلاف الحكم الشرعي وقد قام الباحث بجمع القراءات القرآنية والوقوف على ما فيها من دلالات وكذلك اختلاف الفقهاء فى المسألة وبيان مذاهبهم ومدى استدلالهم بالقراءات القرآنية وخلصت الدراسة إلى أن القراءات تضيف للفقيه من الأحكام ما لا يستطيع أن يقف عليه لولا علم القراءات. الكلمات الافتتاحية: اختلاف، القراءات، أحكام الوضوء Abstract The Quranic readings (Qiraat) have received the attention of Muslims since their first renaissance at the hands of the Messenger of God and his honorable companions to this day. But one of the topics that did not take its share of the study extensively is the effect of Quranic readings (Qiraat) in other sciences. This study comes to show the impact of the different Qur’anic readings on the legal rulings and deals with the rulings of purity related to ablution. It includes talking about the impact of the different Qur’anic readings in clarifying the imposition of the two legs, is it washing or wiping? It deals with the effect of the different readings on the ruling on intercourse with a menstruating woman after the blood interruption and before washing, as well as the effect of the different readings on the ruling on invalidating ablution by touching a woman, to show that the different readings had an impact on the difference in the legal ruling. The researcher collected the Qur’anic readings and found out what they contain of indications, as well as the differences of jurists on the issue and their doctrines and the extent of their inference with the Qur’anic readings.